2002
DOI: 10.1002/1615-9314(20021001)25:14<877::aid-jssc877>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of circulating metabolites in drug discovery using high-performance liquid chromatography, and their identification by liquid chromatography coupled with tandem mass spectrometry and nuclear magnetic resonance spectroscopy

Abstract: Isolation of circulating metabolites in drug discovery using high-performance liquid chromatography, and their identification by liquid chromatography coupled with tandem mass spectrometry and nuclear magnetic resonance spectroscopy One of the major components of modern drug discovery is the structural determination and the assessment of biological activity of plasma metabolites. LC-MS/MS has played a prominent role in the identification of metabolites; however, fragmentation patterns alone may not be sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Since the commercial introduction of liquid chromatography/nuclear magnetic resonance (LC/NMR) systems, this hyphenated technique has been mainly applied to the structural elucidation of metabolites in drug development studies12 and to the identification of natural compounds in plant extracts 13. However, recent studies have demonstrated its applicability to the analysis of unknown compounds in environmental samples as 1 H NMR spectra in general give more detailed structural information than mass spectra 14. Optimum structural information is obtained when LC/MS and LC/NMR are used together to identify unknowns in complex mixtures 15.…”
mentioning
confidence: 99%
“…Since the commercial introduction of liquid chromatography/nuclear magnetic resonance (LC/NMR) systems, this hyphenated technique has been mainly applied to the structural elucidation of metabolites in drug development studies12 and to the identification of natural compounds in plant extracts 13. However, recent studies have demonstrated its applicability to the analysis of unknown compounds in environmental samples as 1 H NMR spectra in general give more detailed structural information than mass spectra 14. Optimum structural information is obtained when LC/MS and LC/NMR are used together to identify unknowns in complex mixtures 15.…”
mentioning
confidence: 99%